FORMING OF ENVIRONMENTAL AWARENESS FUTURE SKILLED WORKERS OF THE SEWING INDUSTRY IN INSTITUTIONS OF PROFESSIONAL (VOCATIONAL AND TECHNICAL) EDUCATION (Innovative professional education, 2023)
The conceptual provisions of the formation of environmental awareness of future skilled workers in the clothing industry in an educational institution, the introduction of an environmental component into the content of vocational training are considered.
Keywords: environmental awareness, positive motivation, training content, skilled garment workers